Defending literature in early modern England : Renaissance literary theory in social context - Matz, Robert (Cambridge studies in Renaissance literature and culture ;, 2000)
Robert Matz analyzes the defense of literature in Renaissance England in the context of social transformations particularly affecting the aristocracy. Alongside revisionary accounts of the work of Elyot, Sidney and Spenser, this original study engages with important theoretical work such as Pierre Bourdieu's and offers a substantial critique of New Historicist theory.